Navigating climate, conflict and migration: Insights from Ethiopia and the East and Horn of Africa - Villa, Victor; Chepngetich, Brenda; Zapp, Christopher; Carvalho Magalhaes, Melissa Branca (2025)
The report examines the intricate relationship between climate, human security and migration in Ethiopia and the broader East and Horn of Africa with the goal of informing regional mobility governance. It draws data from IOM's Flow Monitoring Survey from February 2018 to May 2024.